2022
DOI: 10.3389/fmed.2022.898725
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Industry Evaluation of the Effectiveness and Efficiency of the ZaZiBoNa Collaborative Medicines Registration Initiative: The Way Forward

Abstract: IntroductionThe common technical document (CTD) format harmonised the requirements for the registration of medicines, which had traditionally differed from country to country, making it possible for countries to collaborate and conduct joint reviews of applications. One such collaborative medicines registration initiative is the Southern African Development Community ZaZiBoNa, established in 2013. A recent study was carried out with the nine active member regulatory authorities of the ZaZiBoNa to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Some of the challenges of the ECOWAS-MRH initiative namely, lack of centralised submission and tracking which were identified by the applicants in the study were also identified by the NMRAs in the previous study ( Owusu-Asante et al, 2022 ). Similar to the studies conducted with regard to the EAC-MRH and ZaZiBoNa ( Ngum et al, 2022 ; Sithole et al, 2022 ), these challenges were also reported with regard to the respective regional MRH initiatives. In addition, the applicants in this study identified other challenges that were specific to the ECOWAS-MRH initiative such as differences in regulatory performance of the countries and dependence on the countries’ process for communication with applicants, and lack of detailed information on the process for applicants.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Some of the challenges of the ECOWAS-MRH initiative namely, lack of centralised submission and tracking which were identified by the applicants in the study were also identified by the NMRAs in the previous study ( Owusu-Asante et al, 2022 ). Similar to the studies conducted with regard to the EAC-MRH and ZaZiBoNa ( Ngum et al, 2022 ; Sithole et al, 2022 ), these challenges were also reported with regard to the respective regional MRH initiatives. In addition, the applicants in this study identified other challenges that were specific to the ECOWAS-MRH initiative such as differences in regulatory performance of the countries and dependence on the countries’ process for communication with applicants, and lack of detailed information on the process for applicants.…”
Section: Discussionsupporting
confidence: 75%
“…Data for the study were obtained through completion of the Process Effectiveness and Efficiency Rating (PEER) questionnaire ( Ngum et al, 2022 ; Sithole et al, 2022 ) by applicants between October 2022 and January 2023.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the CTD guidelines is “to provide harmonised medicines registration procedures using the CTD in order to improve access to essential medicines for prevention and treatment of priority disease conditions in the East African region” ( EAC Secretariat, 2014 ). According to Sithole et al (2022) , the CTD format has helped to improve work sharing and the harmonisation of registration requirements and joint reviews in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The AMRH initiative's goal was for NRAs within each of Africa's regional economic communities (RECs) to address this problem by coordinating their activities, relying on the work of one another and other trusted regulatory authorities, and applying other principles of smart regulation [5]. Specifically, NRAs within an REC would harmonize technical requirements and standards for medical products regulation, perform joint reviews of marketing authorization applications and joint inspections of manufacturing sites, and increase the use of reliance and cooperation in regulatory matters related to medical products [3,[6][7][8][9]. The resulting improvements in regulatory efficiency would make it easier and faster for medicines manufacturers to register quality products [3,10].…”
Section: Introductionmentioning
confidence: 99%